Our Family Heritage The Stories of Those Who Came Before Us - John B Pelletier 3 Oct 1947 - (Thomaston, ME Indie Authur Books, 2022)
The majority of stories of "Those who came before us" takes us back to the earl 1900s through the 1950s and 1960s. The dynamics of the Acadian families during this timeframe are described as they relate to the joining of the Pelletier, Dionne, Charette and Michaud families living in Northern Maine's St. John Valle, specifically Van Buren. The 1916 death of a young woman at childbirth changes the lives of her siblings and their families, who accepted the children of their recently deceased sister. This practice of accepting children of one's family was more of a common practice then than we experience in the early twenty-first century. This custom repeats itself in the next, after the death of one parent at a young age. The stories also describe the customs and traditions families experienced during this same period of time, highlighting the giving nature of many people "who came before us."